Sue Williamson - Life and work - Gevisser, Mark 1964- (Skira, 2015)
Sue Williamson: Life and Work brings together for the first time all the significant works of one of South Africa's most highly respected and celebrated artists, created over more than thirty years. It starts with her challenging work in the most oppressive days of apartheid, records the heady days of liberation and tracks the difficulties of transformation."